A Japanese nationwide survey of 23-valent pneumococcal capsular polysaccharide vaccine (PPSV23) revaccination coverage rate among elderly adults aged 65 and older and physician's attitude. Issue 9 (1st September 2020) - Nakamura, Atsushi; Kawakami, Kenji; Wakana, Akira; Folaranmi, Temitope A.; Iino, Tomoharu
ABSTRACT: In July 2017, the Japanese Association for Infectious Diseases issued guidance for the administration of the PPSV23 revaccination. Despite increasing recognition of its protective benefits, levels of PPSV23 revaccination coverage rate in Japanese elderly population are unclear at present. Here, we report the results of a survey to know PPSV23 revaccination rates among elderly patients aged 65 and older. We asked an array of questions related to PPSV23 revaccination to Elderly adults and doctors across Japan via Web-based surveys in June 2018. The sampled population consisted of 5, 085 men and women aged 65 and older. The PPSV23 revaccination coverage rate was estimated by survey questions regarded vaccination counts, intervals, and vaccine type. In addition, 400 internal medicine physicians were surveyed and asked about their reasons for recommending PPSV23 revaccination to elderly patients. In total, 1, 648 elderly adults had received at least one PPSV23 dose; of these, 58 had received it at least twice (revaccination coverage rate: 3.5%). The most commonly cited justification for revaccination with PPSV23 among the surveyed physicians was that the benefits of revaccination exceed the risks of revaccination. In addition, multivariate analysis showed revaccinated status was most strongly associated with recommendations from peers (e.g. spouse, family, friends) among elderly subjects. This study reports PPSV23 revaccination coverage rate among Japanese adults aged 65 and older for the first time and concludes that the coverage rate is very low.